Pros and cons of vitamin D measurements: essential component of quality health care - Yadav, Meena K.; Netterwala, Ali; Yadav, K. S. (International Journal of Research in Medical Sciences, 2016)
Accuracy in vitamin D measurement is very important because methods used by various laboratories have no uniformities; of course it is choice of individuals but quality in care matters. There are five different types of Vitamin D but D2 and D3 are the only types that human can use. Earlier researchers have documented that vitamin D3 is better absorbed and utilized than D2. Studies have showed that vitamin D promoting normal blood glycation, immunity, mood swing and other unusual clinical conditions. It is observed from many reports that the effectiveness of D3 provides the most benefit for the human body but there is quite variations in predictive values of different methods.